Pemakaian Kaedah Iḥtiyāṭ Dalam MS1500: 2009: Prosedur Sembelihan Menurut Perspektif Mazhab Syafii - Wafaa’ Mazlan; Ridzwan Ahmad; Norhidayah Pauzi; Madiha Baharuddin (USIM Press, 2024)
Vol. 27 No. 1 (2022): January Issue